The academic and non-academic factors related to students' subject failing at the journalism department of the university of El Salvador, semester I-2000 - Espinoza Segovia, Ana Lilian; Funes Gil, Susana Evelyn (San Salvador : Universidad de El Salvador, 2002)
Imídeo G. Nérici (1985) points out in his book, “Hacia una Didáctica General Dinámica”, that university teaching should avoid four things. First, university studies should not only aim to prepare students to pass exams. Second, university students should not limit themselves to just take notes and then memorize them. Third, university students should neither play passive roles norlimit themselves to know just what the teacher gives them. Fourth, university students should not be kept away from the problems their community and country face.
Incluye anexos
Tesis (Licenciatura en Idioma Inglés, Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2002
Keywords: Rendimiento académico; Deserción universitaria; Periodismo -- Enseñanza